Case of an infant with hepatic cirrhosis caused by mitochondrial respiratory chain disorder. Issue 4 (5th August 2013) - Enkai, Shigehiro; Koinuma, Sachi; Ito, Reiko; Igaki, Junko; Hasegawa, Yukihiro; Murayama, Kei; Ohtake, Akira
Abstract: The patient had hepatomegaly with liver dysfunction at the age of 1 month. Magnetic resonance imaging performed at the age of 1 year showed multiple nodules of varying size in his liver. We were able to examine the mitochondrial respiratory chain function in the liver biopsy samples because all other differential diagnoses for hepatic cirrhosis had been ruled out. Complex I and IV activities were below the normal level (<30%) of the citrate synthase (CS) ratio. Liver blue native polyacrylamide gel electrophoresis showed an extremely weak complex I and IV band. Liver respiratory chain complexes I and IV were found to be deficient in this patient. The histologic findings were highly suggestive of mitochondrial respiratory chain disorder. Findings of progressive liver cirrhosis changes were observed in magnetic resonance imaging at the age of 5 years. An examination of the mitochondrial respiratory chain function should be performed along with a liver biopsy if mitochondrial respiratory chain disorder is suspected as a possible differential diagnosis of idiopathic hepatitis.